Effect of natural antimicrobial agent (MicroGARD) combined with edible coating (NatureSeal) treatment on fresh‐cut butternut squash. Issue 5 (20th April 2021) - Yang, En; Fan, Lihua; Jiang, Yueming; Doucette, Craig; Fillmore, Sherry; Han, Qinqin
Abstract : Abstract: To improve fresh‐cut produce quality and shelf life, 0.5% or 1.0% MicroGARD ® 730 (MG) as a natural alternative to synthetic chemical preservatives, 2.5% NatureSeal ® (NS) product (vitamin/mineral‐based blends), 0.5% MG combined with 2.5% NS, and 1% MG combined with 2.5% NS were used to treat fresh‐cut butternut squash ( Cucurbita moschata ). The 240 g samples were put into food grade bags and stored at 4 or 7 °C. Microbial population, including aerobic plate counts (APCs), yeast and molds, total coliforms, and quality parameters, including head space O2 /CO2 concentration in package, pH, soluble solids, color, and conductivity, were evaluated after 0, 3, 6, 9, 12, and 20 days of storage. Results showed that after 6 days of storage at 7 °C, APC of check and control samples reached to 2.6 × 10 8 and 1.5 × 10 7 CFU/g, respectively; while they were kept at 10 4 CFU/g (3 to 4 log reduction) in the squash samples treated with 0.5% or 1% MG combined with NS at 7 °C. Similar results were found on squash samples stored at 4 °C for 9 days. The cut squash treated with MG combined with NS had APC ≤ 10 7 CFU/g at 4 °C for about 20 days compared to 9 days in controls or 0.5% MG‐treated samples, and 12 days in 1% MG‐treated or NS‐treated samples, respectively. Considering overall quality and extended shelf life, MG combined with NS was recommended to apply to cut squashes stored at 4 °C. Practical Application: This research provided useful information and practical treatment application for developing fresh‐cut produce with good quality and extended shelf life up to 20 days at 4 °C.